Morphometric study of the corpus cavernosum after anabolic androgenic steroid administration in pubertal and adult rats - Sena,Alessandro de Sousa Mendes de (2015)
PURPOSE: To evaluate the penile morphological modifications of pubertal and adult rats chronically treated with supra-physiological doses of anabolic androgenic steroids. METHODS: Forty-eight male Wistar rats were distributed into four groups: two control groups, 105- and 65-day-old (C105 and C65, respectively) injected with peanut oil (vehicle); and two treated groups, 105- and 65-day-old (T105 and T65, respectively) injected with nandrolone decanoate at a dose of 10 mg Kg-1 of body weight. The rats were injected once a week for eight weeks. The rats were then killed and their penises were processed for histomorphometric analyses. The mean of each parameter was statistically compared. RESULTS: A corpus cavernosum reduction of 12.5% and 10.9% was observed in the T105 and T65 groups, respectively, when compared with their respective control groups. The cavernosum smooth muscle surface density diminished by 5.6% and 12.9% in the T65 and T105 groups, respectively, when compared with their controls. In contrast, the sinusoidal space increased by 17% in the T105 group and decreased by 9.6% in the T65 group. CONCLUSION: The use of supra-physiological doses of AAS promotes structural changes in the rat penis, by altering the proportions of corpus cavernosum tissues, in both pubertal and adult treated animals.